1999
DOI: 10.1021/la9805140
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Acetaldehyde and Crotonaldehyde during Adsorption and Reaction on Anatase and Rutile Titanium Dioxide

Abstract: The adsorption of acetaldehyde and crotonaldehyde on the anatase and rutile polymorphs of TiO2 has been investigated with Fourier transform infrared spectroscopy (FTIR). Chemisorption of acetaldehyde on TiO2 involves a strong interaction between the surface and the carbonyl oxygen, causing a significant shift in the location of the ν(CO) vibrational mode to lower frequencies; no interaction with surface hydroxyl groups was observed. Capacities for acetaldehyde and crotonaldehyde adsorption under conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
113
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 57 publications
16
113
0
1
Order By: Relevance
“…It is observed that the strong peak at 1693 cm -1 decreases in intensity during purging of the reaction cell with synthetic air, while the intensity of the broad peak at 1653 cm -1 increases and a new band appears at 1628 cm -1 . The latter two bands are assigned to the (C=O) and (C=C) vibrations of crotonaldehyde and show that aldehyde condensation occurs on anatase TiO 2 at room temperature, which is consistent with results of previous studies [31,32]. The band observed at 1168 cm -1 can be assigned to the C-C vibration mode in either of the aldehyde species.…”
Section: In Situ Ftir Spectroscopysupporting
confidence: 90%
“…It is observed that the strong peak at 1693 cm -1 decreases in intensity during purging of the reaction cell with synthetic air, while the intensity of the broad peak at 1653 cm -1 increases and a new band appears at 1628 cm -1 . The latter two bands are assigned to the (C=O) and (C=C) vibrations of crotonaldehyde and show that aldehyde condensation occurs on anatase TiO 2 at room temperature, which is consistent with results of previous studies [31,32]. The band observed at 1168 cm -1 can be assigned to the C-C vibration mode in either of the aldehyde species.…”
Section: In Situ Ftir Spectroscopysupporting
confidence: 90%
“…The large red-shift of the carbonyl vibration, compared to the gas-phase value of 1760 cm -1 , indicates that the acetaldehyde is coordinated with a surface site through the carbonyl oxygen, as in -C=O → Ti 4+ [47]. In addition, other absorption bands appear at 1643 cm -1 and 1674 cm -1 , and weaker bands are noted at 1355 cm -1 and 1375 cm -1 .…”
Section: Acetaldehyde Adsorptionmentioning
confidence: 92%
“…Probably, the role of TiO 2 is both to make easier the formation of the formaldehyde-hydrate anion, and to activate the CHO moiety for nucleophilic attack. Acyclonucleosides are bioactive compounds able to pair with natural nucleic bases by Watson -Crick interactions [82]. In the context of prebiotic chemistry, glycerol-derived acyclonucleosides, which are characterized by a vicinal diol moiety (as in 14), have received particular attention, mainly because of the possibility to polymerize after activation as phosphates [83].…”
Section: Chemiomimesis In Formamidementioning
confidence: 99%